(5x-6)^2=25x^2-60x+36. Where did the -60x come from?

Question

(5x-6)^2=25x^2-60x+36. Where did the -60x come from?

in progress 0
Savannah 2 months 2021-10-18T04:51:14+00:00 1 Answer 0 views 0

Answers ( )

    0
    2021-10-18T04:52:52+00:00

    Answer:

    see below

    Step-by-step explanation:

    (5x-6)^2

    This means

    (5x-6)*(5x-6)

    FOIL

    First: 5x*5x = 25x^2

    outer:  5x*-6 = -30x

    inner -6*5x = -30

    last -6*-6 = 36

    Add these together

    25x^2 -30x-30x +36

    Combine like terms

    25x%2 -60x+36

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )